Comparative Analysis of the European Regulatory Framework for C&D Waste Management - Fabiola Colmenero Fonseca; Javier Cárcel-Carrasco; Adolfo Preciado; Aurora Martínez-Corral; Andrés Salas Montoya (Advances in Civil Engineering)
This article presents a comprehensive analysis of construction and demolition waste (C&D waste) management in European Union (EU) Member States. The study utilizes official data and reports to assess the current C&D waste management status, revealing substantial disparities in recycling rates across countries, ranging from 100% to 24%. These variations emphasize the importance of knowledge sharing and collaborative efforts to improve C&D waste practices. The paper explores the complex factors influencing C&D waste management performance, offering a nuanced discussion of these dynamics. It provides a comprehensive set of practical strategies to address existing challenges, with a focus on reducing C&D waste sent to landfills or incineration. These recommendations align with the EU’s commitment to sustainable resource management and the transition to a circular economy. The research’s informed measures, driven by environmental responsibility and economic prudence, can significantly diminish C&D waste’s environmental impact. Policymakers, environmentalists, and industry stakeholders can utilize these findings to develop and implement improved C&D waste management practices, promoting sustainability and resource efficiency across the EU. This research contributes valuable insights to the field of C&D waste management, offering a road map for improvement and highlighting the need for collaboration among EU Member States to create a more sustainable and resilient future.